Construction and validation of an educational guide on oral health for elderly included in primary health care (Research, Society and Development, 2023)
The process of caring and educating in health area can occur through instruments, among them, with the Educational Technologies; that favor user participation, contribute to citizenship and develop autonomy. The demographic transition generated changes in the world's population profile. Thus, aging is considered a dynamic and complex process with changes that influence the individual's quality of life. In Brazil, it occurs quickly and intensely and despite being a positive aspect, it brings demands related to the reorganization of Health Care in the Unified Health System. This study aimed to build and validate an educational technology on oral health for elderly people included in the primary health care system in the city of Belém - Pará. After approval by the Research Ethics Committee, a methodological study was carried out with five phases: situational diagnosis, literature review, technology construction, validation and review. The study included 23 health professionals, 13 from other areas and 82 elderly people linked to the Municipal Health Unit Benguí II for the survey of the situational diagnosis, of which 17 participated in the validation. After building the educational technology as an educational guide, it underwent content, appearance and semantic validation, respectively; and after analysis, the educational guide was approved by the corresponding Validation Indexes for each target audience. The educational technology on oral health for the elderly proved to be a valid and adequate instrument to be distributed to primary care professionals and the target audience, being an effective instrument to provide valuable information about health and also acts as a bridge for dialogue.